Sukuk issuance in the emerging markets-a relative evaluation - Khudari M.; Saad N.M. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The Sukuk market in Malaysia runs parallel with the conventional bonds market and provides investors with investment options whereby the market trading is open to all. Indeed, Malaysia has proven itself as a center of choice for foreign corporations to issue Sukuk as well as to invest in these areas, as it offers one of the most diverse (in terms of types of securities, tenures, asset classes, structures, issuers and risk profiles), innovative and sophisticated array of investment choices in the global market. Thus, the objectives of this study are to investigate the significant mean different of amount Sukuk issue between Malaysia and across emerging market economies. The secondary data will be utilized to achieve the study objective for almost 10 countries that issue Sukuk from 2000 until 2015. The data then will be analyzed by using ANOVA or post Hoc test comparison as well as Levenes test. The results prove that Malaysia is a leader in the Sukuk market in terms of largest Sukuk issuer and Sovereign Sukuk and there is a significant mean different between Sukuk issuance by Malaysia and other countries. BEIESP.